2009
DOI: 10.3168/jds.2009-2249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding grass or red clover silage cut at two maturity stages in dairy cows. 1. Nitrogen metabolism and supply of amino acids

Abstract: This study investigated the effects of plant species (red clover vs. timothy-meadow fescue) and forage maturity at primary harvest (early vs. late cut silage) on rumen fermentation, nutrient digestion, and nitrogen metabolism including omasal canal AA flow and plasma AA concentration in lactating cows. Five dairy cows equipped with rumen cannulas were used in a study designed as a 5 x 5 Latin square with 21-d periods. The diets consisted of early-cut and late-cut grass and red clover silage, respectively, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
85
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 32 publications
19
85
3
3
Order By: Relevance
“…These findings agree with previous red clover versus grass silage comparisons Merry et al, 2006;Vanhatalo et al, 2009). Greater NMN with RC is reported to result from a lower N degradability in the rumen Merry et al, 2006;Vanhatalo et al, 2009) and has been attributed to the PPO activity inherent in red clover protecting dietary protein (Lee et al, 2004;Merry et al, 2006;Halmemies-Beauchet-Filleau et al, 2014). However, in the current study, no difference was observed between treatments when the flow of NMN was reported as a percentage of N intake (62.5%), which coincidentally is also greater than previously reported for forage silage diets (33.8%; Merry et al, 2006), further indicating a likely overestimation of duodenal flow in the current study.…”
Section: Nitrogen and Aa Metabolism Across The Rumensupporting
confidence: 93%
See 4 more Smart Citations
“…These findings agree with previous red clover versus grass silage comparisons Merry et al, 2006;Vanhatalo et al, 2009). Greater NMN with RC is reported to result from a lower N degradability in the rumen Merry et al, 2006;Vanhatalo et al, 2009) and has been attributed to the PPO activity inherent in red clover protecting dietary protein (Lee et al, 2004;Merry et al, 2006;Halmemies-Beauchet-Filleau et al, 2014). However, in the current study, no difference was observed between treatments when the flow of NMN was reported as a percentage of N intake (62.5%), which coincidentally is also greater than previously reported for forage silage diets (33.8%; Merry et al, 2006), further indicating a likely overestimation of duodenal flow in the current study.…”
Section: Nitrogen and Aa Metabolism Across The Rumensupporting
confidence: 93%
“…Greater total N flows entering the duodenum with RC than with either PR or CO were in agreement with previous results comparing red clover with grass Merry et al, 2006;Vanhatalo et al, 2009) and in part can be attributed to the greater N content of the RC. The greater total N flow with the RC diet was composed mainly of NMN (dietary, endogenous, and ammonia N).…”
Section: Nitrogen and Aa Metabolism Across The Rumensupporting
confidence: 92%
See 3 more Smart Citations